Intrinsic dynamic and static nature of each HB in the multi-HBs between nucleobase pairs and its behavior, elucidated with QTAIM dual functional analysis and QC calculations. Issue 41 (1st July 2020) - Nakanishi, Waro; Hayashi, Satoko; Nishide, Taro
Abstract : Each HB in nucleobase pairs (Nu–Nu′) has the nature close to that of a molecular complex, for example. Energies for the formation of Nu–Nu′ are linearly correlated with the summarized values of the compliance constant of each HB in Nu–Nu′. Abstract : The intrinsic dynamic and static nature of each HB in the multi-HBs between nucleobase pairs (Nu–Nu′) is elucidated with QTAIM dual functional analysis (QTAIM-DFA). Perturbed structures generated using coordinates derived from the compliance constants ( C ii ) are employed for QTAIM-DFA. The method is called CIV. Two, three, or four HBs are detected for Nu–Nu′. Each HB in Nu–Nu′ is predicted to have the nature of CT-TBP (trigonal bipyramidal adduct formation through charge transfer (CT)), CT-MC (molecular complex formation through CT), or t-HBwc (typical HB with covalency), while the vdW nature is predicted for the C–H⋯X interactions, for example. Energies for the formation of the pairs (Δ E ) are linearly correlated with the total values of C ii −1 in Nu–Nu′. The total C ii −1 values are obtained by summing each C ii −1 value, similarly to the case of Ohm's law for the parallel connection in the electric resistance. The total Δ E value for a nucleobase pair could be fractionalized to each HB, based on each C ii −1 value. The perturbed structures generated with CIV are very close to those generated with the partial optimization method, when the changes in the interaction distances are very small. The results provide useful insights for better understanding DNA processes, although they are highly enzymatic.